Polite calamities : a novel - Gold, Jennifer (Lake Union Publishing, 2024)
When slow-simmering summer secrets and resentments finally reach the boiling point, everyone is at risk of being burned. Polite Calamities explores what "community" really means when societal survival is at stake, and what happens when women decide it's time to stop behaving and start living.